Introducing M-Tool: a standardised and inclusive mental model mapping tool - Van den Broek, Karlijn; Klein, Sina; Luomba, Joseph; Fischer, Helen (System dynamics review, 2021)
Stakeholder mental model elicitation can produce valuable insights into perceptions of complex systems such as ecosystems, economies, or the climate. These mental models can uncover crucial differences in perceptions between stakeholders and prevalent misunderstandings of the system, which can ultimately contribute to successful resource management. This paper introduces a novel tool to capture mental models: M-Tool. M-Tool was designed to be user-friendly for diverse samples, and standardized to ease aggregation and comparison of mental models. With this tool, participants create influence diagrams with a fixed set of pictograms representing the system variables, and weighted arrows to display their relations. M-Tool can be used to identify differences or changes in mental models or to co-produce knowledge with stakeholders and develop strategies to address challenges within the system. This paper describes how to tailor the tool to a research project and discusses how M-Tool may be suitable for diverse research applications. © 2021 The Authors. System Dynamics Review published by John Wiley & Sons Ltd on behalf of System Dynamics Society.